Exploring the Role of Breast Density on Cancer Prognosis among Women Attending Population-Based Screening Programmes. (27th November 2019) - Domingo, Laia; Sala, Maria; Louro, Javier; Baré, Marisa; Barata, Teresa; Ferrer, Joana; Carmona-Garcia, Maria Carmen; Comas, Mercè; Castells, Xavier; CAMISS Study Group,
Abstract : Background . Our aim was to assess the role of breast density on breast cancer mortality and recurrences, considering patient and tumour characteristics and the treatments received among women attending population-based screening programmes. Methods . We conducted a retrospective cohort study among women aged 50–69 years attending population-based screening programmes, diagnosed with invasive breast cancer between 2000 and 2009, and followed up to 2014. Breast density was categorised as low density (≤25% dense tissue), intermediate density (25–50%), and high density (≥50%). Cox proportional hazards regression models were fitted to estimate the adjusted hazard ratios (aHR) and 95% confidence intervals (95% CI) for death and recurrences, adjusting by patient characteristics, mode of detection (screen-detected vs. interval cancer), and tumour features. Results . The percentage of deaths and recurrences was higher among women with intermediate- and high-density breasts than among women with low-density breasts (p = 0.011 for death; p = 0.037 for recurrences). Adjusted Cox proportional hazards regression models revealed that women with intermediate- and high-density breasts had a higher risk of death than women with low-density breasts, being statistically significant for intermediate densities (aHR = 2.19 [95% CI: 1.16–4.13], aHR = 1.44 [95% CI: 0.67–3.1], respectively). No association was found between breast density and recurrences. Conclusions . Breast density was associated with a higher risk of death, but not of recurrences, among women participating in breast cancer screening. These findings reinforce the need to improve screening sensitivity among women with dense breasts and to routinely assess breast density, not only for its role as a risk factor for breast cancer but also for its potential influence on cancer prognosis.